What would I do? Perspectives on the factors underlying Lynch syndrome genetic testing and results sharing decisions for high‐risk colorectal cancer patients. Issue 4 (8th November 2021) - Tiernan, Gabriella; Freeman, Victoria; Morrow, April; Hogden, Emily; Canfell, Karen; Kang, Yoon‐Jung; Taylor, Natalie
Abstract: Objective: Universal tumour testing for Lynch syndrome (LS) in all incident colorectal cancers (CRCs) and sequential diagnostic genetic testing is cost‐effective in Australia. Because of this, our study aimed to understand factors underlying possible decisions faced by tumour test‐positive CRC patients and their at‐risk relatives throughout the LS diagnosis pathway. Methods: Semi‐structured telephone interviews were conducted with 23 participants, using four hypothetical scenarios. Vignette‐guided closed‐ and open‐ended questions asked about LS genetic testing uptake, discussing diagnosis with at‐risk relatives, and risk‐reducing interventions. Personal perspectives on genetic testing were collected pre‐post vignette discussion. Inductive thematic analysis was performed on open‐ended questions. Decisional pathway diagrams were developed to convey factors influencing complex decision‐making processes. Results: Participant responses incorporated unfolding scenario information, resulting in three decision themes: (1) wanting to know one's LS status; (2) informing family about LS; (3) navigating risk‐reducing interventions. Across all themes, 'knowledge' emerged as a facilitator, and 'negative emotional experience' as a barrier. Personal supportive views toward genetic testing increased post‐interview. Conclusions: When communicating with tumour test‐positive CRC patients or their relatives about LS genetic testing, providing guidance/resources to inform decisions around risk‐reducing interventions and informing family members is critical. Scenario‐driven interviews provide insight into what individuals might do when facing complex healthcare decisions and could aid informed decision‐making. This approach may be applicable in other conditions, particularly with mainstreaming being increasingly introduced into the genetic context.